An Overview of the Management and Rehabilitation of Dysphagia - Mari Nakao-Kato; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Dysphagia is a medical condition that makes it difficult for a person to eat or swallow. It is estimated that 590 million people worldwide have dysphagia. The causes are varied and include neurological disorders like stroke and motor neuron disease, head and neck cancer, neuromuscular diseases, inflammatory diseases such as dermatomyositis, dementia, cervical spinal cord injury, and anterior vertebral ossification. The assessment and screening of dysphagia consists of a questionnaire-based interview, mealtime observation, and, if deemed necessary by a screening test or instrumental examination by specialists. Treatment is based on the diagnosis, patients’ cognition and information gathered by screening and clinical evaluation. Patient’s function can be improved only when treatment is comprehensive and includes compensatory feeding using an adjusted swallowing diet, compensatory posture adjustment, and nutritional improvement. We present a brief overview of the assessment and management strategies for dysphagia Keywords: deglutition disorder, dysphagia, rehabilitation, disease management